Beyond Collective Supervision: Informal Social Control, Prosocial Investment, and Juvenile Offending in Urban Neighborhoods. (23rd March 2015) - Leech, Tamara G. J.
Abstract : This article examines prosocial investment and supervision of youth as separate indicators of informal social control. Data from 599 survey respondents in 90 Indianapolis, IN, block groups indicate that, at the neighborhood level, the relationship between these two variables and delinquency during early and middle adolescence varies by severity of offense. Specifically, negative binomial models reveal an inverse relationship between supervision and both status offenses and misdemeanors, but the relationship with misdemeanors is stronger in areas with higher levels of prosocial investment. In contrast, prosocial investment has an inverse association with felony charges. Overall, these results call for future quantitative scholarship that contextualizes neighborhood‐level supervision and that is attentive to neighborhood support and empowerment assets in models of urban adolescent delinquency.